Pengembangan Pariwisata Melalui Penggunaan dan Pengoptimalan Media Digital - Mahendra Galih Prasaja; Endah Pri Ariningsih; Fatah Pinanggih Arizki (FKIP, Universitas Palangka Raya, 2024)
Knowledge and understanding about how to use and apply social media in promotional or business activities for tourism actors or the public is very important. Some of the main problems faced by service partners are related to the use and optimization of social media. If the community or tourism actors already have an understanding of these things, their business can grow more rapidly. The aim of implementing this community service is to provide strengthening and understanding of management concepts such as marketing, use of digital media, to develop business for the community or tourism actors in promoting tourist attractions in Tlogokotes Village as service partners. The activity mechanism uses lecture and discussion methods as well as practice or simulation. Each session ends with a question and answer session to find out how far the participants' level of understanding is in responding to the material that has been presented. This community service activity was carried out in three sessions by each team member, and it was carried out well. As a result, service partners can have better knowledge and understanding of management concepts, because the response and enthusiasm of service partners to understand the material presented is quite high. As a recommendation, community service with this theme can be carried out with other service partners such as home industry groups, street vendor groups, traditional market trader groups and so on, so as to expand understanding of management concepts such as Sharia marketing, product packaging and financial management. business better.